Climate change and developing world: The snares of learning by doing - Cavallucci, Olga (2010)
The article includes three main bodies: a first one, in which the global climate change situation is analyzed, in the frame of the post-Copenhagen agenda, with special attention to developing countries. A second part, in which the attitude of the so called ALBA Group towards this international agenda is specifically considered and scrutinized; finally, a part, in which the path ahead is analyzed: challenges, expectations, possible scenarios.